PENGARUH LAJU PERTUMBUHAN INFLASI, HARGA MINYAK DUNIA DAN DOW JONES INDUSTRIAL AVERAGE TERHADAP INDEKS HARGA SAHAM GABUNGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007-2011 - Pratama, Rully Putra Surya; Kurniawati, Indah (Universitas Ahmad Dahlan, 2013)
This research attempts to influence the inflation growth, the oil price dow jones industrial average to Composite Stock Price Index which is registred in indonesian stock exchange in the period of 2007-2011. The population in this research was the whole index in indonesian stock exchange (ISE). The sample was taken based on sampling purpodive. The data analysis technique used double linier regression. The dependent variable in this research was the growth of Composite Stock Price Index, while the independent variable was the inflation growth, the oil price and dow jones industrial average. The results of this research showed that the almost dependent variable used had effects for the growth of Composite Stock Price Index. The inflation rate growth variable did not have effects on Composite Stock Price Index growth, while the oil price rate variable and dow jones industrial average had effects on Composite Stock Price Index growth. Simultaneously, the independent variables examinedhere had effects on Composite Stock Price Index growth.